Estado del arte de las representaciones mediáticas en la teoría Queer - Galindo Suscal, Jennifer Vanessa (2018)
In this article a state of the art is realized about visibility and representation of the Queer theory, in virtual and traditional media. This state compares the research on how to represent in the media. The corporality and behavior in the face of sexual and gender diversity. The investigations revolve around narratives in television series, movies and on the Web. The work questions the way in which identities are visualized, from the perspective of several authors, considering that the media raise a narrative in stereotypes from the patriarchal. The discussions focus on feminism as a starting point to talk about the Queer theory. The approaches of gender, sex, sexuality, sexual orientation and identity are part of a social and cultural construction In this work you will find positions among normative, subversives and transgressors. In order to understand Queer theory, it is about building relationships that are not close to what is called "weird". Not only is talking about the aesthetics of the body but how love relationships are created that are often hidden for fear of social rejection. In spite of the queer proposal, normalized forms of love are not observed in the media or in everyday life, because falling in love can be quite diverse. The conclusions mention that what is relevant are rights as human beings without the need to categorize the “other”.